2020
DOI: 10.13005/ojc/360612
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on Size and Concentration of Silver Nanoparticles Synthesized using Ixora coccinea Linn. Leaf Extracts

Abstract: The synthesis of silver nanoparticles via plant-mediated approach is an emerging area of research interest worldwide. The procedure is cost-effective and does not require the use of toxic chemicals and complicated reaction conditions. In the present investigation, silver nanoparticles were prepared using the leaf extracts of Ixora coccinea Linn., a common ornamental shrub in the Philippines, as the reducing agent. The effect of pH on the synthesis was investigated, and results showed that the quality of the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Basic pH generally formed AgNPs with smaller and narrower size distribution. This result is in line with the previous study’s findings [ 12 ]. The compound containing the carboxyl group tends to have a better reduction potential at basic pH from the structure-activity properties.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Basic pH generally formed AgNPs with smaller and narrower size distribution. This result is in line with the previous study’s findings [ 12 ]. The compound containing the carboxyl group tends to have a better reduction potential at basic pH from the structure-activity properties.…”
Section: Discussionsupporting
confidence: 94%
“…Natural plant pH can vary in different areas of the plant and have an impact on plant extract antioxidant activity [ 8 , 9 , 10 ]. The experimental pH is of great interest as this has been shown to influence the size and shape of resultant metallic nanoparticles [ 11 , 12 ]. Morones et al (2005) demonstrated the size-dependent bactericidal properties produced by AgNPs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a greener strategy, the use of biological substances as the reducing agents instead of toxic reagents such as sodium borohydride has been demonstrated to be superior due to its low cost and eliminates toxic synthesis by-products 8 . Such biomolecules utilized in the synthesis of silver nanoparticles are carbohydrates 9,10 and plant extracts 7,11,12 .…”
Section: B E S I D E S T H E T H E R M a L M E T H O D Amentioning
confidence: 99%